2004
DOI: 10.1002/bip.20032
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of different experimental dimeric structures of the SL1 sequence from the genomic RNA of HIV‐1 in solution: A molecular dynamics simulation and electrophoresis study

Abstract: SL1 is a stem-loop RNA sequence from the genome of HIV-1 thought to be the initiation site for the dimerization of the retroviral genomic RNA. The aim of this study is to check the stability in solution of different experimental dimeric structures available in the literature. Two kinds of dimer have been evidenced: an extended duplex looking like a double helix with two internal bulges and a kissing complex in which the monomers with a stem/loop conformation are linked by intermolecular loop-loop interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…40 We have not seen any visible correlation between the dynamics of flanking bases and stem melting. Interestingly, such stem instability has been reported in AMBER simulation of kissing complexes performed by Aci et al 49 but not in our extensive AMBER simulations. The reason of this difference is presently not clear to us.…”
Section: Comparison Of Charmm and Amber Simulationsmentioning
confidence: 66%
See 3 more Smart Citations
“…40 We have not seen any visible correlation between the dynamics of flanking bases and stem melting. Interestingly, such stem instability has been reported in AMBER simulation of kissing complexes performed by Aci et al 49 but not in our extensive AMBER simulations. The reason of this difference is presently not clear to us.…”
Section: Comparison Of Charmm and Amber Simulationsmentioning
confidence: 66%
“…Bulged-in/out conformations, some flanking bases are bulged-in whereas others remain bulged-out, bases do not form inter-strand stacking; (left), A272, A273, A272* are bulged-in, whereas A273* is bulged-out (simulation F2); (right), A273 is bulged-in, A272* and A273* are bulged-out, A272 makes hydrogen bond across the strands to the phosphate oxygen of A273* (shown in green) (simulation B3). 49 showed destabilization of the X-ray kissing complexes (melting of the stems), not observed by Reblova et al 46 Concerning MD simulations of the Mujeeb's NMR structure for DIS-B, the Reblova's simulations revealed large scale rearrangements in very early stages of the run, indicating that the initial structure is unrelaxed. In contrast, Aci et al 49 reported a globally stable trajectory with rearrangements at the stem-loop junction.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In vivo experiments have also suggested that dimerization is a two-step process as a conformational rearrangement of the dimeric RNA incorporated in the virion is observed during maturation. 31 Although many structural studies have been devoted to SL1, [26][27][28][29][30][32][33][34] very little is known about the conformational pathway of the KC/ED transition. On the basis of model building from the X-ray structure of KC, it was suggested that the transition could occur via cleavage and cross-religation process at the level of purines located at the stem-loop junction without disruption of any existing WatsonCrick base-pairs in KC.…”
Section: Introductionmentioning
confidence: 99%